ADVANCES, CHALLENGES, AND FUTURE DIRECTIONS IN HYDRAULIC ENGINEERING: A COMPREHENSIVE REVIEW OF STRUCTURES, PROCESSES, AND SUSTAINABILITY - Khalimov Ibrokhimjon (Journals Park Publishing, 2025)
This article presents a comprehensive analysis of contemporary trends, technological advancements, and persistent challenges in hydraulic engineering, with a special focus on the design, construction, and sustainability of hydraulic structures such as dams, weirs, channels, and water distribution networks. Drawing on a wide spectrum of international case studies and recent scientific literature, the paper critically evaluates the intersection of hydrology, material science, structural analysis, environmental impact assessment, and modern management practices in the field. Key topics include advances in modeling and simulation, the integration of ecohydraulic principles, adaptation to climate variability, risk and reliability assessment, sediment transport, as well as the application of digital technologies such as remote sensing and artificial intelligence. The article further explores policy frameworks and the socioeconomic implications of large-scale hydraulic projects, proposing integrated approaches to ensure long-term resilience, resource efficiency, and environmental protection. Ultimately, this work contributes both a state-of-the-art scientific synthesis and a forward-looking perspective for researchers, practitioners, and policymakers involved in the development and stewardship of hydraulic infrastructure.
Keywords: Hydraulic engineering, hydraulic structures, water management, dams, sustainability, sediment transport, climate change, digital technologies, ecohydraulics, risk assessment.